Pengembangan Alat Pendeteksi Kebocoran Gas LPG Menggunakan Sensor Mq-2 Sebagai Upaya Pencegahan Dini Terhadap Risiko Kebakaran - Sahara, Siti; Pragat Pamungkas, Bagas; Firdaus, Ikram Maulana (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to find out how to design a security system that has a role as an LPG gas leak detection tool which is able to detect the presence of polluted gas in the surrounding air which can cause fires using a device, namely the mq-2 sensor and to find out how the gas leak detection tool works. the LPG. In preparing this research, the methodology used was ADDIE which is a development model that focuses on the suitability of the product being designed with the approach used. This research was carried out by carrying out several stages, including the analysis stage, namely analyzing the background and benefits of product development, design is the activity of making a product design, development is the stage of making a product according to the design that has been made, implementation is the application of a product that has been made, evaluation is the stage carried out to evaluate products that have been developed. The way this tool works is by detecting indications of polluted gas in the surrounding air, then the sensor sends a signal to the buzzer to provide a warning in the form of a sound produced by the buzzer.